Three Communication Difficulties of EFL Students - Vargas Jiménez, Grettel (2015)
In spite of the diversity of resources (media, Internet, software, videos, social networks, etc.) many students present a lot of difficulties in developing their communication skills in learning English as a foreign language (EFL). Indeed, there are three aspects that affect the students’ oral production negatively. First, lack of motivation that could be manifested in anxiety and students’ low self-esteem. Second, the learning environment which includes the teacher’s methodology and classroom environment in which the absence of an EFL speaking social context does not provide a natural content to stimulate communication. Third, mother tongue interference that is in trying to develop EFL with non-native speakers learners where students (and teachers) tend to translate everything to the first language; as a result, this practice reduces the possibility of thinking in EFL due to the lack of meaningful situations and real life contexts developed in class. However, the purpose of this article goes beyond proving that these three aspects affect the communicative skills of EFL learners. In fact, its purpose is to provide valuable information about the causes of this problem for improving fluency among EFL learners.